Planeación Financiera en la Estación de Servicio Cooperativa Loja de la Ciudad de Loja. Período 2022-2026 - Ponce Villavicencio, Gabriela Andrea (2023)
The Degree Project entitled: Financial Planning in the Loja Cooperative Service Station in the City of Loja, Period 2022 - 2026, was developed in accordance with the stipulations of the Academic Regulations of the National University of Loja prior to opting for the degree and title of Engineer in Accounting and Auditing Public Accountant-Auditor, which will serve as a contribution to the administrative area and to the partners who can take the necessary corrective measures, and improve the economic and financial situation in order to increase economic benefits in the future. To fulfill the first specific objective, the financial statements were compiled and a diagnosis was made to determine the economic and financial structure; financial indicators of liquidity, profitability, activity and indebtedness for the period 2021 were applied; and a SWOT matrix was prepared to identify the strengths, weaknesses, opportunities and threats, and based on the results obtained, financial planning was carried out. In the second objective, sales and purchase forecasts were prepared using the seasonal index method based on the sales and purchase history obtained on a monthly basis for the year 2021, which resulted in favorable increases for the five years projected; then, cash inflows and outflows were determined to develop the cash budget. The third objective was to prepare pro forma financial statements for the period 2022- 2026, with the purpose of establishing favorable estimates of assets, liabilities, equity, income, costs, expenses, and profit to provide a perspective of the future economic and financial situation to the directors and, based on the results obtained, decisions can be made to contribute to the economic growth of the Service Station. Finally, the break-even point for the five projected years was determined, here was determined the minimum volume of sales that must be made to cover costs and expenses; therefore, by fulfilling the objectives mentioned in this degree work, it is provided with suggestions for solutions detailed in the conclusions and recommendations.